Financial performance of conventional and islamic commercial banking during the Covid-19 Pandemic: A comparative analysis - Sopi Siti Sopiah; Hatta Setiabudhi; Mutia Pamikatsih (Institute of Computer Science (IOCS), 2024)
The differences in fundamental operational principles and models between conventional and Islamic commercial banks raise questions about how the financial performance of these two banks will develop during the pandemic. This study aims to compare the financial performance of conventional and Islamic commercial banks. The ratios analyzed in this research include NPL/NPF, ROA, ROE, BOPO, NIM/NOM, and LDR/FDR. The sample consists of commercial banks that implement dual-system banking and have been registered with OJK as domestic private banks. The data used in this study are secondary data from quarterly financial reports covering the period 2020–2022. The approach used in data analysis is descriptive statistics to provide a general overview of the comparison between conventional and Islamic commercial banks. Furthermore, data normality is tested using the Kolmogorov-Smirnov test to ensure data distribution. Since the data is not normally distributed, the hypothesis testing in this study employs nonparametric statistics, specifically the Mann-Whitney U test. The results of the study indicate that, overall, Islamic commercial banks perform better than conventional commercial banks in terms of financial performance. The hypothesis analysis results reveal differences in the NIM/NOM ratios between conventional and Islamic commercial banks. However, there is no significant difference in the NPL/NPF, ROE, BOPO, and LDR/FDR ratios between the two types of banks